2022
DOI: 10.1007/s40429-022-00413-y
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Vaping Among Youth and Young Adults: a Scoping Review

Abstract: Purpose of Review The purpose of this review was to describe the state-of-the-literature on research specific to cannabis vaping among youth and young adults. Recent Findings Out of 1801 records identified, a total of 202 articles met eligibility criteria for inclusion in this review. Most of this literature (46.0% of studies) was specific to the health effects of cannabis vaping, particularly EVALI (e-cigarette and vaping associated lung injury). Other re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 216 publications
(250 reference statements)
0
17
0
Order By: Relevance
“…Most systematic reviews assessed youth and adult cannabis use as the primary outcome, including one rapid review (O'Grady, 2022), four narrative reviews (Lachance, 2022;Pacula, 2022;, and two meta-analyses . Harrell et al (Harrell, 2022) also examined cannabis use as part of a larger scoping review of factors linked to vaping, and Pacula and colleagues (Pacula, 2022; investigated alcohol use both alone and in combination with cannabis, updating an earlier review by Guttmannova et al . While the reviews' findings are mixed, two broad generalizations hold: increases in cannabis use, when observed, were more likely (i) among young adults than adolescents and (ii) following passage of recreational versus medical cannabis laws.…”
Section: Existing Egms And/or Relevant Systematic Reviewsmentioning
confidence: 99%
“…Most systematic reviews assessed youth and adult cannabis use as the primary outcome, including one rapid review (O'Grady, 2022), four narrative reviews (Lachance, 2022;Pacula, 2022;, and two meta-analyses . Harrell et al (Harrell, 2022) also examined cannabis use as part of a larger scoping review of factors linked to vaping, and Pacula and colleagues (Pacula, 2022; investigated alcohol use both alone and in combination with cannabis, updating an earlier review by Guttmannova et al . While the reviews' findings are mixed, two broad generalizations hold: increases in cannabis use, when observed, were more likely (i) among young adults than adolescents and (ii) following passage of recreational versus medical cannabis laws.…”
Section: Existing Egms And/or Relevant Systematic Reviewsmentioning
confidence: 99%
“…A recent review article found that cannabis vaping is more common among young adults than older adults. 16 Further, national estimates from the 2019 Monitoring the Future College Students and Young Adults Survey showed that 14% of college students and 17% of nonstudents reported past month cannabis vaping which is a substantial increase from 5% to 8% in 2017, respectively. 17 College students who used cannabis more frequently in the past year were over three times more likely to report cannabis vaping than not vaping, 18 indicating this may be a popular ROA for young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reviews and studies found an increasing prevalence of cannabis vaping among the general population in the U.S. and Canada in the past decade [ 6 , 7 , 8 , 9 ]. A 2018 nationally representative survey of 131,807 U.S. adults found that 1.3% reported vaping cannabis in the past month and, among people who used nicotine ‘e-cigarettes’, 7.1% reported vaping cannabis in the past month [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2018 nationally representative survey of 131,807 U.S. adults found that 1.3% reported vaping cannabis in the past month and, among people who used nicotine ‘e-cigarettes’, 7.1% reported vaping cannabis in the past month [ 7 ]. Three recent reviews reported an increasing number of young people vaped cannabis using a personal vaporizer or e-cigarettes between 2013 to 2021 in the U.S. and Canada [ 6 , 8 , 9 ]. A meta-analysis of 17 national studies showed the past month pooled prevalence of cannabis vaping has increased by 5-fold from 1.6% in 2013–2016 to 8.4% in 2019–2020 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation